Assessment of psychiatric comorbidities and sociodemographic profiles of the patients referred to the general hospital psychiatric unit of a tertiary care hospital in Kolkata, West Bengal - Mondal, Arijit; Ghosh, Soumi; Mandal, Uday Sankar; Saha, Dwaipayan (Asian Journal of Medical Sciences, 2021)
Background: According to the previous studies, psychiatric symptoms are high in patients with physical illness, but the referral rates are much below expectation. Aims and Objectives: Here a descriptive cross-sectional study has been conducted using self designed semi structured proforma to asses the socio demographic profile and psychiatric diagnosis of patient with physical illness referred from other departments in a tertiary medical care centre for consultation liaison (C-L) psychiatry care. Materials and Methods: The study population consists of the patients referred to psychiatry department for consultation purpose from all the other departments in a 4 months period. The data were collected on a self designed semi structured pro forma and all the diagnosis were made according to International Classification of Disease -10 (ICD-10) criteria. Analysis has been done using descriptive statistics. Results: A total numbers of 203 patient has been referred to psychiatry department during the study period . Among them 144 were inpatient and 59 were outdoor based referral. Majority were female, married . The maximum referral were from general medicine department followed by neuromedicine. Most common reason of referral being suicidal attempt by different means followed by patients having depressive features .The most common psychiatric diagnosis was depression followed by delirium. Conclusion: C-L psychiatry plays a significant role in better evaluation and management of patients with psychiatric comorbidities referred from non-psychiatric departments.